Chemical profiling and characterization of phenolic acids, flavonoids, terpene glycosides from Vangueria agrestis using ultra‐high‐performance liquid chromatography/ion mobility quadrupole time‐of‐flight mass spectrometry and metabolomics approach. (2nd June 2020) - Avula, Bharathi; Bae, Ji‐Yeong; Wang, Yan‐Hong; Wang, Mei; Osman, Ahmed Galal; Smith, Kerri; Yuk, Jimmy; Ali, Zulfiqar; Plumb, Robert; Isaac, Giorgis; Khan, Ikhlas A.
Abstract: Vangueria agrestis is a shrub indigenous to tropical Africa, belonging to family Rubiaceae and is traditionally used as a decoction for treatment of fever, pain, and malaria. This study was undertaken to investigate the chemical constituents based on precursor exact mass and fragment ion information. The chemical profiling and structural characteristics of chemical constituents from methanolic extracts of dried aerial parts and roots of V. agrestis and dietary supplements were analyzed using ultra‐high‐performance liquid chromatography/ion mobility quadrupole time‐of‐flight mass spectrometry coupled with UNIFI platform and multivariate analysis in both negative and positive ion modes. A non‐targeted ultra‐high‐performance liquid chromatography‐mass spectrometry analysis was carried out to profile the chemical constituents of crude extracts of V. agrestis, and 73 compounds, including reference compounds, were identified. The fragments of flavonoids, monoterpene, and triterpene glycosides revealed the characteristic cleavage of glycosidic linkages, and the fragmentation pattern provided the identity of the sugars. This analytical method provides a quick method for quality assessment of dietary supplements. Finally, a chemometrics approach with multivariate statistical tools was used to visualize the differences between root and aerial parts of plant samples and to find the potential chemical markers that differentiate among these parts of V. agrestis samples and dietary supplements.